1996
DOI: 10.1007/s002239900148
|View full text |Cite
|
Sign up to set email alerts
|

Neridronate Preferentially Suppresses the Urinary Excretion of Peptide-Bound Deoxypyridinoline in Postmenopausal Women

Abstract: ELISAs for measuring the urinary excretion of collagen crosslinks and related peptides appear to show marked differences in sensitivity to anti-resorptive therapy. This presumably reflects variations in specificity of the anylate being detected in these assays, and the way in which they respond to treatment. To clarify these points, we used HPLC analysis to assess the effect of four weeks treatment with the amino-bisphosphonate, neridronate, on free and peptide-bound fractions of the collagen cross-links deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…Our results are consistent with earlier reports of a much smaller decrease in urine free Dpd, compared with peptide markers NTx and CTx, in response to bisphosphonate therapy, 19,21,24,35 hormone replacement therapy23,24 and calcium supplementation.P Cross-linked telopeptides of type I collagen appear to most sensitively reflect the change in bone resorption in these diverse therapies.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with earlier reports of a much smaller decrease in urine free Dpd, compared with peptide markers NTx and CTx, in response to bisphosphonate therapy, 19,21,24,35 hormone replacement therapy23,24 and calcium supplementation.P Cross-linked telopeptides of type I collagen appear to most sensitively reflect the change in bone resorption in these diverse therapies.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, D-Pyr could re¯ect collagen breakdown in other tissues, but this seems unlikely [1,4,17]. These data further support the hypothesis that the telopeptides are cleaved differently from D-Pyr, accounting for differences in the decrease from baseline with risedronate therapy [15]. After risedronate was discontinued, resorption rates began to increase, but NTx and CTx remained slightly below baseline values at 10 weeks after treatment.…”
Section: Discussionsupporting
confidence: 54%
“…One possible explanation for this is a change in the handling of these degradation products in the kidney [16]. Alternatively inhibition of osteoclastic activity by bisphosphonates could involve not only a change in the absolute rate of bone resorption but also a change in the pattern of collagen breakdown products [15]. One possible explanation for this difference is that the pattern is dependent on the rapidity of bone resorption [1].…”
Section: Discussionmentioning
confidence: 99%
“…Garnero et al [12] reported large changes in the peptidebound crosslinks (e.g., NTX and CTX), smaller changes in the total PYD and DPD and no change in the free PYD and DPD in response to bisphosponate therapy in patient with Paget's disease and osteoporotic postmenopausal women, but similar changes in excretion of free, total and peptide-bound PYD and DPD following hormone replacement therapy in postmenopausal women. According to some studies [13,14,15,17], but not others [16], it has been proposed that when going from a low to a high bone turnover state (such as the postmenopausal period), excretion of free PYD and DPD is increased less than the excretion of total PYD and DPD and peptide-bound crosslinks.…”
Section: Discussionmentioning
confidence: 99%
“…These assays could represent a valuable alternative to the more difficult HPLC technique [5,[9][10][11]. Since the metabolic origins of the urinary free and bound crosslinks are unknown, it is not certain that the determination of free, peptide-bound or total pyridinium crosslink excretion will provide similar information in different clinical situations [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%